Variations in TM6SF2, PCSK9 and PCSK7 genes and risk of hepatic steatosis after liver transplantation: a cross-sectional study - Ahad Eshraghian; Elham Moasser; Negar Azarpira; Mohammad Reza Fattahi; Saman Nikeghbalian; Seyed Ali Malek-Hosseini; Bita Geramizadeh (BMC Gastroenterology, 2021)
Abstract Background Genetic abnormalities might have important role in pathogenesis of hepatic steatosis after liver transplantation. We aimed to investigate association between genetic variations in transmembrane 6 superfamily member 2 (TM6SF2) rs58542926, proprotein convertase subtilisin/kexin type 9 (PCSK9) rs505151 and proprotein convertase subtilisin/kexin type 7 (PCSK7) rs2277287 with hepatic steatosis in liver transplant recipients. Methods In a cross-sectional study, adult (> 18 years) liver transplant recipients who were referred for their routine post-transplant follow-up between June 2018 and September 2018 were included in the study. Hepatic steatosis in transplant recipients was assessed by controlled attenuation parameter (CAP). Polymerase chain reaction-restriction fragment length polymorphism (PCR–RFLP) was used to study TM6SF2 rs58542926, PCSK7 rs2277287 and PCSK9 rs505151 genotypes. Results 107 liver transplant recipients were included. There was no association between different genotypes of PCSK9 rs505151 and PCSK7 rs2277287 with hepatic steatosis in liver transplant recipients (P value > 0.05). The presence of TT genotype of TM6SF2 rs58542926 was higher in patients with hepatic steatosis measured by CAP after liver transplantation. In patients with moderate and severe hepatic steatosis (grade 2 and 3 steatosis), AG + GG genotypes of PCSK9 rs505151 were more prevalent than AA genotype (OR 8.667; 95% CI 1.841–40.879; P value = 0.004) compared to patients with mild steatosis (grade 1). In multivariate regression model, AG + GG genotypes of PCSK9 rs505151 were associated with moderate and severe steatosis in liver transplant recipients (OR 5.747; 95% CI 1.086–30.303; P value = 0.040). Conclusions Genetic variations in TM6SF2 rs58542926 and PCSK9 rs505151 might be associated with hepatic steatosis in liver transplant recipients.